RANCANG BANGUN PROTOTIPE PEMBANGKIT LISTRIK TENAGA UAP DENGAN TURBIN IMPULS DIAMETER 70 CM - Susilowati, Sri Endah; Budiman, Arif (Universitas 17 Agustus 1945 Jakarta, 2023)
AbstractThe increasing electricity needs of the Indonesian people at this time have a fairly large number, PLN as the electricity provider who is responsible for supplying electricity is quite overwhelmed in meeting the electricity needs of the Indonesian people. This is because the territory of Indonesia is very large, the population is large, and the energy sources for power generation using fossil fuels are very limited. So the researchers made an Impulse Turbine design (De Laval) to find a more efficient source of electrical energy for people who are far from the reach of PLN. The De Laval Turbine is a part of the Impulse Turbine that utilizes potential energy and converts it into kinetic energy. The De Laval turbine is the simplest turbine consisting of one stage, namely a set of nozzles and a row of blades, with the meaning that the pressure of the incoming steam to the outgoing steam is carried out in one nozzle on one row of blades (one level). The rotor speed is too high to maintain high efficiency. The maximum rotational speed of the De Laval turbine when coupled to the generator is 5050 RPM which produces a voltage of 5.5 Volts. When given a load, at a pressure of 5 bar the De Laval turbine can produce a maximum power of 24,197Watt with efficiency 33.03%Keywords: Power Plant, De Laval Turbine, Energy, EfficiencyAbstrakMeningkatnya kebutuhan listrik masyarakat Indonesia pada saat ini memiliki memiliki jumlah yang cukup besar, PLN sebagai pihak penyedia listrik yang bertanggung jawab sebagai penyuplai listrik cukup kewalahan dalam memenuhi kebutuhan listrik bagi masyarakat Indonesia. Hal ini dikarenakan Wilayah Indonesia yang sangat luas, jumlah penduduk yang banyak, serta sumber energi pembangkit listrik menggunakan bahan bakar yang berasal dari fosil sangat terbatas. Maka peneliti membuat sebuah rancang bangun Turbin Impuls (De Laval) untuk mencari sumber energi listrik yang lebih efisien untuk masyarakat yang jauh dari jangkauan PLN. Turbin De Laval yaitu merupakan bagian dari Turbin Impuls yang memanfaatkan energi potensial dan merubahnya ke kinetik.Turbin De Laval adalah turbin paling sederhana terdiri dari satu tingkat, yakni satu set nosel dan satu baris sudu, dengan arti tekanan uap masuk hingga uap keluar dilaksanakan dalam satu nosel pada satu baris sudu (satu tingkat). Diperlukan kecepatan rotor yang